2009
DOI: 10.1139/z09-064
|View full text |Cite
|
Sign up to set email alerts
|

Female effect on antlers of pampas deer (Ozotoceros bezoarticus)

Abstract: Size and bone mineralization of deer antlers are related to testosterone concentrations, and antler cast is observed after withdrawal of testosterone concentration. Our objectives were to determine if (i) contact with hinds stimulates antler development and increases hard antler period length in pampas deer ( Ozotoceros bezoarticus (L., 1758)) and (ii) antlers from males that were or were not in contact with hinds differ in colour. While 5 males were in breeding paddocks consisting of 1 adult stag and 5–10 hin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Scaling relationships between body size and antler size have usually been estimated among species (Gould 1974; Clutton-Brock et al 1980; Plard et al 2011; Lemaître et al 2014; Tidière et al 2017, 2020). The fewer number of studies that have estimated antler scaling relationships within a cervid species have either estimated an ontogenetic scaling relationship or static scaling relationships, but few have estimated both (Stewart et al 2000; Ungerfeld et al 2011; Melnycky et al 2013; Jones et al 2018; Tidière et al 2020). Our estimates of static scaling relationships between body mass and antler mass reflected the findings from the ontogenetic scaling relationship.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Scaling relationships between body size and antler size have usually been estimated among species (Gould 1974; Clutton-Brock et al 1980; Plard et al 2011; Lemaître et al 2014; Tidière et al 2017, 2020). The fewer number of studies that have estimated antler scaling relationships within a cervid species have either estimated an ontogenetic scaling relationship or static scaling relationships, but few have estimated both (Stewart et al 2000; Ungerfeld et al 2011; Melnycky et al 2013; Jones et al 2018; Tidière et al 2020). Our estimates of static scaling relationships between body mass and antler mass reflected the findings from the ontogenetic scaling relationship.…”
Section: Discussionmentioning
confidence: 99%
“…Scaling relationships are often estimated to summarize relationships between body mass and sexually selected traits such as antler size (Gould 1974; Clutton-Brock et al 1980; Ditchkoff et al 2001; Plard et al 2011; Lemaître et al 2014; Tidière et al 2017, 2020). There are numerous studies estimating interspecific body–antler size scaling relationships, but fewer intraspecific studies (Stewart et al 2000; Ungerfeld et al 2011; Melnycky et al 2013; Jones et al 2018). Intraspecific studies are needed to examine how a trait develops with body mass from young to old age regarding factors that might constrain growth and antler size (Pélabon et al 2013; Jones et al 2018).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Antler cycle is closely related to androgen concentrations (Bubenik 1990b) and several studies on cervids have observed that artificially elevated testosterone delays normal antler casting (Lincoln et al 1972, Semepere andBoissin 1982). Late antler casting is not uncommon amongst individuals in good condition within cervid populations, for example male pampas deer (Ozotoceros bezoarticus) in the presence of females cast their antlers later compared to male-only groups (Ungerfeld et al 2009) which indicates increased testosterone levels. Female white-tailed deer that remain in estrus or come into estrus late may cause extended periods of elevated testosterone levels in males and result in late antler casting which may explain the late-breeding male retaining antlers until at least 14 April 2019 and the antlered male documented on 15 April 2020 represent additional observations of late antler casting for this region.…”
Section: Discussionmentioning
confidence: 99%